Evaluation of using Smart Office Applications at PDAM Kota Balikpapan - Alfiansyah, Emil Robert Kaburuan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to evaluate using the Smart Office application at PDAM Balikpapan. Based on the results of the analysis in this study, it was found that: (1) external variables have a positive and significant effect on the perceived ease of use of the application, the better the appearance of the program, the use of colors and shapesof the program, the higher the user's perception of the ease of use of Smart Office; (2) external variables have a positive and significant effect on perceptions of application usability, the better the appearance of the program, the use of colors and forms of the program, the higher the user's perception of the benefits of using Smart Office; (3) perceived ease of use affects the perception of Smart Office application usability, the higher the user's perception of the ease of the Smart Office application, the higher the user's perception of the benefits of the Smart Office application; (4) perceived ease of use has a positive and significant effect on usage intention, the higher the user's perception of the ease of use of the application, the higher the user's interest in using the application; (5) perceived usefulness has a positive and significant effect on usage intentions, the higher the user's perception of the benefits of the application, the higher the user's interest in using the application; (6) Facilitation conditions have a positive and significant effect on intention to use, the better the facilities that condition using Smart Office applications, the higher the user's interest in using Smart Office; (7) Social influence has a positive and significant effect on intention to use, the higher the social influence obtained by users for using Smart Office, the higher the user's interest in using Smart Office.